DAMPAK PENGARUH PENGGUNAAN APLIKASI VIDEO LIVE STREAMING DI SMARTPHONE PADA KALANGAN PELAJAR - Ryan Ari Setyawan; Yumarlin MZ (Jurnal Informatika Komputer, Bisnis dan Manajemen, 2019)
This study aims to determine the effect of using live streaming video applications that are currently popularly used by students. Live streaming video application itself is a video sharing application that is broadcast live and real time so that users can broadcast what activities are done and can be watched by everyone who has the same application and account. For interaction users can make two-way video calls with other users or interactions through the chat service provided. These applications are in the market such as Bigolive, Live.me, Ome.tv, Instagram live and others. This research was conducted using regression analysis. The analysis results obtained from this study that the use of live streaming video applications among students does have an impact on students such as students rarely attend religious activities, often make noise in class, often toy smartphones during lessons and even 51.58% talk dirty.